ڕۆڵی فیلمی فێرکاری لە پەرەپێدانی چەمکە کۆمەڵایەتییەکان لای منداڵانی باخچە - ئەحمد, خەرمان عوسمان; خالد, پ.ى.د. حسن فخرالدین (Sulaimani Journal for Humanities, 2021)
This current study aimed at studying the effect of the educational film in developing some of the social concepts for kindergarten children aged 5-6 and identifying the differences among the mean scores of answers to the experimental group based on gender variables. The researcher provided three probabilities, and this method applied for the research sample consisting of (40) children of which (20) were male, and (20) female which are implemented on (sulaymaniyah) kindergarten children for the academic year (2019-2020). To achieve this goal, the researcher applied experimental method using experimental group and controlling group. The researcher provided (10) educational films and visual aids for social concepts to kindergarten children consisting of (28) units of subjective questions including (14) selection units, (11) matching units, and (3) drawing units, after verification of the validity and reliability of the scale. To find statistic solutions and analysis, via combined knowledge and data in the research community, the researcher used the (SPSS) program to analyze the data and the research concluded the following results: 1- The effectiveness of using educational films in developing social concept for kindergarten children aged (5-6). 2- There is a difference of a statistical level (0.05) between the means of scores of individual answers of controlling group and experimental group in applying the social concept test in the interest of the experimental group.